Chemical Composition Control of Evaporated Cu2ZnSnS4 Solar Cells (Journal of Solar Energy Research Updates, 2021)
This paper focuses on chemical composition issue of evaporated Cu2ZnSnS4 (CZTS) absorber and potential solutions to it. The chemical composition of the CZTS absorber was estimated by energy dispersive spectroscopy (EDS) and a solution-based Inductively Coupled Plasma Mass Spectroscopy (ICPMS). It discloses a chemical non-uniformity issue spatially on even the same sample and confirms Sn loss issue. It also reveals that substrate option affects composition control.